Isolation and Characterization of an Anti-Osteoporotic Compound from Melia toosendan Fructus - Seong Cheol Kim; Dong Ryun Gu; Hyun Yang; Sung-Ju Lee; Jin Ah Ryuk; Hyunil Ha (MDPI AG, 2023)
Melia toosendan fructus, traditionally employed in traditional Chinese and Korean herbal medicine, exhibits diverse biological properties encompassing anti-tumor, anti-inflammatory, and anti-viral effects. However, its influence on bone metabolism remains largely unexplored. In this study, we investigated the impact of an ethanolic extract of Melia toosendan fructus (MTE) on osteoclast differentiation and characterized its principal active constituent in osteoclast differentiation and function, as well as its effects on bone protection. Our findings demonstrate that MTE effectively inhibits the differentiation of osteoclast precursors induced by receptor activator of nuclear factor κB ligand (RANKL). Utilizing a bioassay-guided fractionation approach coupled with UHPLC-MS/MS analysis, we isolated and identified the triterpenoid compound toosendanin (TSN) as the active constituent responsible for MTE's anti-osteoclastogenic activity. TSN treatment downregulated the expression of nuclear factor of activated T cells c1, a pivotal osteoclastogenic transcription factor, along with molecules implicated in osteoclast-mediated bone resorption, including tumor necrosis factor receptor-associated factor 6, carbonic anhydrase II, integrin beta-3, and cathepsin K. Furthermore, treatment of mature osteoclasts with TSN impaired actin ring formation, acidification, and resorptive function. Consistent with our in vitro findings, TSN administration mitigated trabecular bone loss and reduced serum levels of the bone resorption marker, C-terminal cross-linked telopeptides of type I collagen, in a mouse bone loss model induced by intraperitoneal injections of RANKL. These results suggest that TSN, as the principal active constituent of MTE with inhibitory effects on osteoclastogenesis, exhibits bone-protective properties by suppressing both osteoclast differentiation and function. These findings imply the potential utility of TSN in the treatment of diseases characterized by excessive bone resorption.